Matrix effects in the C 1s photoabsorption spectra of condensed naphthalene - Schmidt, Norman Anja; Wenzel, Jan; Dreuw, Andreas (The journal of chemical physics, 2016)
High-resolution C 1s near-edge x-ray absorption fine structure (NEXAFS) spectra of naphthalene are investigated. By comparing the spectral signatures of condensed naphthalene molecules with those of naphthalene in the gas phase, we are able to unambiguously identify spectral features which are affected by the intermolecular interactions in the condensed phase. With the help of calculations using time-dependent density-functional theory and the second-order algebraic-diagrammatic construction scheme for the polarization propagator, resonances in the relevant energy range can be assigned to valence and Rydberg-like excitations. Thus, we obtain a more detailed identification of NEXAFS resonances beyond the present literature.